Automatic Extraction of Doppler Envelopes for Gait Analysis Using FMCW Radar: A Novel Approach for Spatio-Temporal Parameters Estimation - Sumin Kim; Hyun-Chool Shin (Applied Sciences, 2025)
This study presents a novel method for automatically extracting Doppler envelopes from Frequency-Modulated Continuous Wave (FMCW) radar signals for gait analysis. In contrast to conventional percentile-based approaches that require manual selection of Doppler envelopes for specific body parts (Spine, Leg, and Foot), the proposed contour-based method enables fully automated estimation of representative speed values from the Doppler map. Experiments were conducted on five participants with varying physical characteristics, and key gait parameters—such as walking speed, step length, and stride time—were estimated and compared against motion capture-based ground truth. The proposed method demonstrated relative errors typically below 10%, with key parameters such as Foot Speed and Leg Speed falling below the commonly cited 5% clinical threshold. Paired t-tests revealed no statistically significant differences between the proposed estimates and the ground truth across all gait parameters (<semantics>p>0.05</semantics>), supporting the method’s accuracy and reliability.